2000
DOI: 10.1038/sj.ejhg.5200518
|View full text |Cite
|
Sign up to set email alerts
|

Structural interpretation of mutations in phenylalanine hydroxylase protein aids in identifying genotype–phenotype correlations in phenylketonuria

Abstract: Phenylalanine hydroxylase (PAH) is the enzyme that converts phenylalanine to tyrosine as a rate-limiting step in phenylalanine catabolism and protein and neurotransmitter biosynthesis. Over 300 mutations have been identified in the gene encoding PAH that result in a deficient enzyme activity and lead to the disorders hyperphenylalaninaemia and phenylketonuria. The determination of the crystal structure of PAH now allows the determination of the structural basis of mutations resulting in PAH deficiency. We pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 52 publications
5
27
0
1
Order By: Relevance
“…of a different amino acid residue to the properties of the residue that is normally present in the wild-type protein, it can be apparent that an important interaction between amino acids is lost, or that the replacement amino acid cannot be accommodated in a given space without seriously perturbing the surrounding environment. For catalogues of illustrative examples see Erlandsen and Stevens [1999] and Jennings et al [2000a].…”
Section: Modulation Of the Mutant Protein Phenotype In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…of a different amino acid residue to the properties of the residue that is normally present in the wild-type protein, it can be apparent that an important interaction between amino acids is lost, or that the replacement amino acid cannot be accommodated in a given space without seriously perturbing the surrounding environment. For catalogues of illustrative examples see Erlandsen and Stevens [1999] and Jennings et al [2000a].…”
Section: Modulation Of the Mutant Protein Phenotype In Vitromentioning
confidence: 99%
“…As expected from the primary sequence, those amino acid residues that are altered as a result of disease-causing mutations are found to be distributed very widely throughout the structure. The 3D location and structural contacts of those individual amino acid residues have been documented [Erlandsen and Stevens, 1999;Jennings et al, 2000a]. In some cases, but not all, this can help illuminate the effects of a mutation upon protein function or structure, or generate hypotheses which may then be tested by IVE analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The large number of possible allelic combinations makes prediction of the phenotype difficult (Dipple and McCabe, 2000;Scriver and Kaufman, 2001;Kasnauskiene et al, 2003;Kim et al, 2006;Bercovich et al, 2008;Danielle et al, 2009). In vitro expression analysis studies have demonstrated a large range of residual activities among different mutations (null to 75%) (Waters et al, 1998;Jennings et al, 2000;Waters, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A structural model of phenylalanine hydro xylase was completed (14)(15)(16) and the location, along with structural contacts of individual amino acid residues, was documented (7,17). This provided the base for a molecular modeling of the mutation effect in silico (18).…”
Section: Defective Phenylalanine Hydroxylasementioning
confidence: 99%